The validity and reliability of the MyJump2 application to assess vertical jumps in trained junior athletes - Rogers, S. A.; Hassmen, P.; Hunter, A.; Alcock, A.; Crewe, S. T.; Strauts, J. A.; Gilleard, W. L.; Weissensteiner, J. R. (Measurement in Physical Education and Exercise Science, 2019)
This study aimed to assess the validity and reliability of jump assessments using the MyJump2 application. Eleven junior athletes (15 ± 1.4 years) performed five countermovement (CMJ) and drop jumps (DJ) measured simultaneously by a force platform and MyJump2. Additionally, intra- and inter-day reliability was assessed over two sessions, 7 days apart. Extremely high agreement between MyJump2 and the force platform (intra-class correlation coefficient, ICC = 0.99) and the intra- and inter-operator agreement (ICC = 0.98-0.99) confirmed the validity and reliability of MyJump2. Mean typical errors (coefficient of variation percentage, CV%) within the first and second sessions were 4.9% and 4.5% respectively for CMJs, and 8.0% to 11.8% for DJ outcomes. CMJ height held acceptable inter-day reliability (CV < 10%; ICC > 0.8), while DJ did not. Results supported MyJump2 to be a valid and reliable tool for assessing jumps; however, with variability in DJs in this cohort, appropriate caution should be taken if including in a junior assessment battery.